Raw pig blood consumption and potential risk for Streptococcus suis infection, Vietnam. - Huong, V; Hoa, N; Horby, P; Bryant, J; Van Kinh, N; Toan, T; Wertheim, H (Centers for Disease Control and Prevention (CDC), 2014)
We assessed consumption of raw pig blood, which is a risk factor for Streptococcus suis infection in Vietnam, by using a mix-method design. Factors associated with consumption included rural residency, age, sex, occupation, income, and marital status. We identified risk groups and practices and perceptions that should be targeted by communication programs.